Sistema de costos de producción de cacao para mejorar la rentabilidad en la finca El Edén recinto Guamag-Yacu, cantón Echeandía, provincia de Bolívar, año 2017 - Arana Silvera, Martha Justina (2018)
The present research work is focused on obtaining the costs of cocoa production and elaboration of the process cost system. The objective was to establish a system of cocoa production costs to improve profitability in the "El Edén" farm, Guamag-Yacu site, Echeandía canton, Province of Bolívar. For this, the descriptive, deductive and analytical-synthetic methods were used to obtain the information, with which it was possible to determine the processes that are carried out in the cocoa crop, which are the records that must be done in a cost system by processes. It was non-experimental because no variable was manipulated; applied, because the principles of cost accounting were used as the basis of the investigation. The techniques were document analysis, structured interview, survey and interview. As part of the results, it is concluded that the producers do not keep records of the expenses they make in any of the processes or production, nor of income; do they not know the costs of production, and the point of equilibrium that they must reach.